PENGARUH PEMBERIAN JUS TOMAT DAN JERUK NIPIS TERHADAP KADAR GLUKOSA DARAH PADA WANITA DEWASA USIA 40 – 60 TAHUN - Wulan Nur Fitriani; Mohammad Jaelani; Arintina Rahayuni (JURNAL RISET GIZI, 2017)
Background : DM is a chronic disease, not infrequently patients with DM depends on drugs throughout life. Drug consumption brings economic impact besides side effects of course. Therefore it is necessary alternative treatment in preventing the occurrence of DM disease by using vegetables and fruits. Based on the results of Riskesdas 2013, DM prevalence increased from 1.1 percent (2007) to 2.1 percent, while in Semarang there was an increase from 13,112 cases (2013) to 15,464 cases (2014). The highest prevalence in Semarang that is in Kecamatan Pedurungan with working area of Tlogosari Wetan by 8.6%.Objective  : To determine the effect of tomato and lime juice on blood glucose levels in adult women aged 40-60 years.Methods  : This research was clinical nutrition research. The type of research was true experiment that used randomized pretest posttest control group design. The sample size is 20 treatments and 18 controls. The test used to determine the difference of blood glucose level between the treatment group and the control group is Independent T-test and to determine the effect of tomato juice and lime juice on blood glucose control with nutrient intake is ANOVA Repeated Measure Test.Results  : Based on statistical tests showed that in subjects with initial blood glucose high category (≥90 mg / dl) there was more decrease in blood glucose in the treatment group even though statistically not significant (p = 0,354). Subjects with initial blood glucose normal category (90 mg / dl) there was decrease in blood glucose even though statistically not significant (p = 0,139).Conclusion  : Tomato and lime juice can decrease blood glucose levels in the research subjects, although statistically not significant.